Evaluating Participatory Planning: A case study of Taipei’s urban regeneration projects - Yu, Hsin-ko (A+BE | Architecture and the Built Environment, 2025)
This research examines the impact of participatory planning on the realisation of public interests in urban regeneration, establishing an analytical framework to assess how participation shapes spatial transformations. Focusing on Taipei, it investigates the roles of public and private actors, statutory participatory processes, and resulting spatial changes. Two primary objectives guide the study: proposing a framework for assessing participatory processes and spatial outcomes and analysing Taipei’s diverse urban regeneration approaches—private-led, public-led, and social housing as a regeneration strategy. Six key questions explore literature on participation, evaluation indicators, policy evolution, implementation practices, spatial influences, and the effects of statutory methods like public hearings. Grounded in communicative planning thought, the research introduces the Inclusive Radar, adapted from Fung’s Democracy Cube, with axes for Participant, Communication and Decision-Making, Authority and Power, and Spatial Transformation. Employing case-study methodology, it integrates semi-structured interviews, site visits, meeting notes analysis, and cross-case comparisons. Findings reveal property-owning stakeholders’ dominance, marginalising non-property-owning stakeholders despite participatory processes. Private-led projects prioritise procedural compliance, public-led ones mediate via community planners but hinge on owners’ consent, and social housing fosters distrust through ambiguous participation. Overall, structures favour property rights, sidelining broader public interests like accessible facilities and green spaces. The study concludes that pre-assumed public interests restrict participation, with policy shifts emphasising property rights transfer and real-estate incentives. The Inclusive Radar offers a multidimensional tool for future applications, advocating policy reforms, capacity-building, and stronger public interest definitions to enhance inclusivity.